A new species of kukri snake (Colubridae: Oligodon Fitzinger, 1826) from the Phnom Samkos Wildlife Sanctuary, Cardamom Mountains, southwest Cambodia - Neang, Thy; Grismer, L. Lee; Daltry, Jennifer C. (Zootaxa, 2012)
A new species of kukri snake Oligodon Fitzinger, 1826 is described from the Phnom Samkos Wildlife Sanctuary, Carda-mom Mountains, southwest Cambodia. Oligodon kampucheaensis sp. nov. differs from other Indochinese and SoutheastAsian species of Oligodon by having 15–15–15 dorsal scale rows; 164 ventral scales; 39 subcaudal scales; anal plate un-divided; deep bifurcated hemipenes, lacking papillae and spines extending to subcaudal scale 11; 17 transverse cream andblack-edged bands on body; three bands on tail; eight or nine scales long between dorsal bands; white ventrolateral spotson the lateral margin of every dark brown squarish or subrectangular ventral blotch. The hemipenial characters place it asthe tenth species of the O. cyclurus group but it has a lower dorsal scale count than other species in this group. The dis-covery of this species from the Phnom Samkos Wildlife Sanctuary increases the number of kukri snakes for Cambodia to ten and indicates the importance of additional field studies in the Cardamom Mountains.